Life Satisfaction Considering Job and Business: A Case Study in University of Sargodha - Ali, Asad; Ahmed, Irfan; GulZaman, Malik; Kajal, Rubaisha; Javed, Madiha (International Journal of Asian Social Science, 2017)
Job and business are the social activities which subsist in every one’s life in one way or the other way. It is not a new phenomenon it is as old as the history of mankind itself. In this study, a questionnaire on comparison of life satisfaction considering job and business is developed on Likert scale which covers approximately all the aspects of job and business. For collecting opinions, Sargodha city was chosen and defined a sample of 384 respondents. Then respondents were selected with simple random sampling by whom questionnaires were filled. Overall results of this study depicts that respondents are in favor of job and feel more satisfaction in their life as compare to in business. All the work was done on Statistical Package for the Social Sciences (SPSS) software.